Cytomegalovirus reactivation in esophageal cancer patients receiving chemoradiotherapy: A retrospective analysis. (13th September 2021) - Kitagawa, Koichi; Okada, Hideaki; Miyazaki, Shuichiro; Funakoshi, Yohei; Sanada, Yukinari; Chayahara, Naoko; Mayahara, Hiroshi; Fujii, Masahiko
Abstract: Background: Although rare, cytomegalovirus (CMV) reactivation can be lethal in patients with cancer. However, the criteria for the prevention of cytomegalovirus reactivation during cancer treatment are unclear. This study aimed to identify factors associated with CMV reactivation in patients with esophageal cancer who were receiving chemoradiotherapy. Methods: This retrospective study included esophageal cancer patients receiving definitive or palliative chemoradiotherapy during April 2013–March 2020. Patients with fever during chemoradiotherapy underwent a systemic work‐up to detect the primary focus of infection, and CMV antigenemia was assessed in cases of unidentifiable infection. Results: Among 132 patients (80.3% male, median age 69 years [range, 39–86 years]), 124 received 5‐fluorouracil plus cisplatin and 8 received oxaliplatin–5‐fluorouracil–levofolinate chemotherapy. Overall, 19 patients had CMV reactivation, 37 had other infections, and 76 had no identified infection (groups 1, 2, and 3, respectively). Median minimum lymphocyte counts were 81.0/µl (interquartile range: 52.0–144.0/µl), 120.0/µl (81.0–162.5/µl), and 185.5/µl (120.5–328.0/µl) in groups 1, 2, and 3, respectively, with counts being significantly lower in groups 1 and 2 than in group 3 ( p  < 0.001). In multiple logistic regression analysis, the minimum lymphocyte count was associated with CMV reactivation (odds ratio 0.983, 95% confidence interval: 0.973–0.994, p  = 0.002). Conclusion: CMV reactivation is not rare in patients with esophageal cancer who were receiving chemoradiotherapy and is associated with the minimum lymphocyte counts. CMV reactivation should be considered during differential diagnosis for patients with a severe decline in lymphocyte counts when receiving chemoradiotherapy. Abstract : CMV reactivation is not rare in esophageal cancer patients receiving chemoradiotherapy and is associated with minimum lymphocyte counts. CMV reactivation should be considered in differential diagnosis when a patient receiving chemoradiotherapy presents with a marked decrease in the lymphocyte count.